Penyelesaian Satu Atap Perkara Judicial Review Di Mahkamah Konstitusi - Muhammad Ishar Helmi (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2019)
Abstract.After the integration of the judiciary, the Supreme Court has a very large responsibility which previously only managed judicial techniques (examining, adjudicating and deciding cases) and administration at the Supreme Court level, but after that the Supreme Court had to manage judicial and organizational techniques, administration , and the finance in the Supreme Court and the Judicial Agency below is supplemented by the authority of judicial review of legislation under the Act. However, with unification, cassation and authority judicial review can lead to accumulation of cases in the Supreme Court, so that this is contrary to the principle of fast justice and low costs and legal certainty will be ruled out. In addition, cases of judicial review at the Supreme Court also exclude the principle of audi et alteram partem, namely the statement heard by the parties in the trial, while the proceedings in the Supreme Court do not adhere to the principle as in the Constitutional Court which is open to the public.Keywords: Judicial Review, Audi et Alteram Partem, Constitutional Court. Abstrak.Setelah adanya penyatuatapan lembaga peradilan, Mahkamah Agung memiliki tanggung jawab yang sangat besar yang sebelumnya hanya mengelola teknis yudisial (memeriksa, mengadili, dan memutus perkara) dan administrasi di tingkat Mahkamah Agung, akan tetapi setelah itu Mahkamah Agung harus mengelola teknis yudisial dan organisasi, administrasi, serta finansial di Mahkamah Agung dan Badan Peradilan di bawahnya ditambah lagi dengan kewenangan judicial review peraturan perundang-undangan di bawah Undang-Undang. Namun, dengan penyatuatapan, kasasi dan kewenagan judicial review dapat mengakibatkan menumpuknya perkara di Mahkamah Agung, sehingga hal tersebut bertentangan dengan asas peradilan cepat dan biaya ringan serta kepastian hukum akan dikesampingkan. Selain itu, perkara judicial review di Mahkamah Agung juga mengenyampingkan prinsip audi et alteram partem yakni keterangan didengarkan oleh para pihak di dalam persidangan, sedangkan proses persidangan dalam Mahkamah Agung tidak menganut prinsip seperti di Mahkamah Konstitusi yang bersifat terbuka untuk umum. Kata Kunci: Judicial Review, Audi et Alteram Partem, Mahkamah Konstitusi